Mouse Genome Database (MGD)-2017: community knowledge resource for the laboratory mouse. Issue Volume 45:Issue D1(2017) (24th November 2016) - Blake, Judith A.; Eppig, Janan T.; Kadin, James A.; Richardson, Joel E.; Smith, Cynthia L.; Bult, Carol J.; ,
Abstract: The Mouse Genome Database (MGD: http://www.informatics.jax.org ) is the primary community data resource for the laboratory mouse. It provides a highly integrated and highly curated system offering a comprehensive view of current knowledge about mouse genes, genetic markers and genomic features as well as the associations of those features with sequence, phenotypes, functional and comparative information, and their relationships to human diseases. MGD continues to enhance access to these data, to extend the scope of data content and visualizations, and to provide infrastructure and user support that ensures effective and efficient use of MGD in the advancement of scientific knowledge. Here, we report on recent enhancements made to the resource and new features.